3D-Printed Reconfigurable Communication System Based on Tunable Liquid Crystals - Pietschmann, Simon; Shi, Jing; Bachbauer, Felix; Gold, Gerald; Maune, H. (2025 IEEE Wireless and Microwave Technology Conference, WAMICON 2025, 2025)
This paper presents an additively manufactured communication system for V-Band applications using a 2 × 2-Antenna array in which each element can be controlled by an individual liquid crystal (LC) based phase shifter. To integrate the anisotropic material into the feed structure, a cavity made of UV-curable photopolymer resin is printed using stereolithography. A targeted beam steering angle of 7° was achieved, while the measured gain of the phased antenna array was between 16.18 dB and 14.02 dB at a center frequency of 62.5 GHz.
CRIS-Team Scopus Importer:2025-06-20
Keywords: additive manufacturing; inter-satelite links; liquid crystal; phase shifter; phased antenna array

3D Printed Transmission Type Phase Shifter Based on Tunable Liquid Crystals - Pietschmann, Simon; Bilchenko, F.; Maune, H.; Shi, Jing; Bachbauer, Felix; Gold, Gerald (2024 54th European Microwave Conference, EuMC 2024, 2024)
This work presents an additively manufactured transmission phase shifter operating at 60 - 65 GHz based on the relative permittivity change obtained from rotating anisotropic liquid crystals (LC) by an external field. A slotted waveguide structure is filled with a printed inlay that provides the cavity for holding the LC material. To reduce the reflection at the transition from the empty to the filled waveguide, various types of inlays are being investigated.
CRIS-Team Scopus Importer:2024-12-13
Keywords: additive manufacturing; liquid crystal; phase shifter; reconfigurable components; slotted waveguide

Additively Manufactured Circular Polarized V-Band Phased Antenna Array - Shi, Jing; Pietschmann, Simon; Bachbauer, Felix; Akula, V.; Maune, H.; Gold, Gerald (2025 IEEE Wireless and Microwave Technology Conference, WAMICON 2025, 2025)
Due to the demand for inter-satellite V-band communication between CubeSats, a circular polarized phased shifted 1 × 4 horn antenna array was designed. The whole structure includes two parts, the 1 × 4 linear polarized horn antenna array, manufactured with Selective Laser Sintering-Fine Details Resolution (SLS-FDR) technology, and a circular polarizer that was manufactured with Projection Micro Stereolithography (P μ SLA). With the help of waveguides of different length, the antenna array could be measured at a phase difference of 120°. They serve as placeholders and are included to be replaced by liquid crystal (LC) phase shifters in later application. The beam steering angle of the 1 × 4 antenna array reached 10° and 11°. The measured axial ratios (AR) at the two steering angles are 2.84 dB and 3.61 dB.
CRIS-Team Scopus Importer:2025-06-20
Keywords: Additive Manufacturing; Circular Polarization; CubeSats; LC Phased Antenna Array; P muSLA; SLS-FDR; V-band

Additively Manufactured Phase-Shifted Antenna Array Model in V-Band - Shi, Jing; Akula, V.; Bachbauer, Felix; Pietschmann, Simon; Maune, H.; Gold, Gerald (2024 54th European Microwave Conference, EuMC 2024, 2024)
A proposed design for a compact liquid crystal (LC) V-Band phased antenna array for inter-satellite links between CubeSats was unveiled, which includes an antenna array, feeding network, and LC phase shifter. In this work, a 4x4 horn antenna array with a corporate feeding network and length varied waveguides as an alternative to LC phase shifter were printed, which was supported with fine detail resolution (FDR) additively manufacturing technology. The phased antenna array was tested at 62.5 GHz with beam steering at 6°, 12°, and 18°, and its gain ranged from 23.79 dB to 18.65 dB in the azimuth plane and from 23.36 dB to 16.65 dB in the elevation plane.
CRIS-Team Scopus Importer:2024-12-13
Keywords: CubeSat; FDR additively manufacturing; feeding network; inter-satellite links; LC phase shifter; phased antenna array; V-Band

Design and Additive Manufacturing of an E-Plane 1-to-9 Power Divider for Satellite Communication - Bachbauer, Felix; Pietschmann, Simon; Shi, Jing; Gold, Gerald (2025 IEEE Radio and Wireless Symposium (RWS), 2025)
A very compact power divider concept in rectangular waveguide technology is presented, whereby the divider can basically be adapted to the required number of outputs. A 1-to-9 divider is shown as an example in this article. This novel divider concept is particularly suitable for applications with special requirements in terms of weight and space, such as miniature satellites, i.e. CubeSats. It is intended to be placed between the power amplifier and the phase shifter. The phase shifters are also designed as waveguides, thus avoiding conventional multi-stage dividers. The use of a quasi sector horn-shaped structure results in a very light weight and compact component. Additive manufacturing of the plastic base body with subsequent metalization and the slotted waveguide technology also ensure considerable weight saving
CRIS-Team Scopus Importer:2025-04-01
Keywords: power dividers; additive manufacturing; space communication; CubeSat